Genomewide SNP marker identification associated with drought tolerance in oil palm - Dwi Yono; Yogo Adhi Nugroho; Zulfikar Achmad Tanjung; Condro Utomo; Tony Liwang (Society for Indonesian Biodiversity, 2021)
Abstract. Yono D, Nugroho YA, Tanjung ZA, Utomo C, Liwang T. 2021. Genomewide SNP marker identification associated with drought tolerance in oil palm. Biodiversitas 22: 3138-3144. Drought stress is one of the abiotic stresses that frequently occurred in the oil palm plantation and has a negative impact on fresh fruit bunch (FFB) production. Therefore, drought-tolerant palms are essential to be selected to mitigate this challenge. In Indonesia, several oil palm plantation areas have a dry climate, such as Lampung province. Distinct yield performance palms were identified from well-recorded agronomic trials in these areas, where the palms are frequently exposed to drought stresses every year and lead them to suffer from water deficit response. Group of high and low-yielding palms was selected based on FFB production of each palm for at least ten constitutive years. The double digest restriction amplified DNA (ddRAD) genotyping methods were used to capture the Single Nucleotide Polymorph (SNP) variant from pools of sample association datasets. At least, 538k SNPs were identified from these pooled datasets. A bulked segregant analysis with a Case-Control approach was implemented to screen the contrast SNP profiles between both pools. A total of 56 association signals was selected from sequential filtering. These SNP sites are located in 21 genes. Further SNP validation and phenotypic verification are necessary to obtain SNPs marker for drought-tolerant palm selections.